Traditional Versus Instructing Standard Guidelines of Preoperative Fasting Times on Associated Discomforts in Patients undergoing Elective Cesarean Section: Orotta Maternity National Referral and Teaching Hospital and Sembel Hospital, Eritrea - Beraki, Michael; Yohannes, Yosief; Geldner, Goetz; McDonough, John (International Journal of Advanced Nursing Studies, 2019)
AbstractIntroduction: Preoperative fasting is vital in preventing pulmonary aspiration, regurgitation and vomiting during the induction of anesthesia. Every patient scheduled for surgery including pregnant mothers need to be on fasting for certain period of time. Women undergoing cesarean section need full energy for themselves and the fetus to overcome the stress of birth. However, fasting time in Eritrea is generally longer than is recommended by American Society of Anesthesiologists. Prolonged fasting time has undesirable effects including, nausea, vomiting, dizziness, thirst, hunger etc. Objectives: This study compared the associated discomforts between traditional versus instructing standard guidelines of fasting times among mothers undergoing elective cesarean section. Methods: A non-randomized clinical trials among 106 mothers was conducted. Two groups for comparisons in two different hospitals were selected. One group received instructions of preoperative fasting according to the American Society of Anesthesiologists Task Force guidelines and the other group followed through the traditional approaches, i.e. â€œnothing by mouth after mid-nightâ€. Results: Mild to moderate degrees of discomforts was seen in the study participants. Feelings of thirst and hunger were the serious discomforts experienced. The associated discomforts were not determined to be significantly different (p=0.256) among the two groups of comparison. Conclusion: The study concluded that the associated discomforts were not statistically different between the traditional and standard groups. There was mild to moderate degrees of discomforts in both groups of study. Though the finding shows similar magnitude of discomforts between the two comparison groups, postoperative discomforts appear to worsen as the timing of fasting increases.